The Use of Contrastive Studies in Linguistics - Bland, Merton L. (Journal of Modern Languages, 2017)
This study considers the needs of the graduate students, especially the linguistics’ ones, in finding an adequate topic to produce a research paper to complete their degrees. The paper suggests students to pay more attention to the SLA’s (Second Language Acquisition) process, as a field within the field of linguistics, by considering the Contrastive Analysis Hypothesis (CAH). It also mentions that considering the CAH helps to find the differences between the native language (Ll) and the target language (L2), which is responsible for the difficulties faced in SLA.